Exponential-type inqualities in Rn and applications to elliptic and biharmonic equations - Federica Sani (Mathematical Sciences, 2013)
Adams'inequality [2] in its original form is nothing but the Trudinger-Moser inequality for Sobolev spaces involving higher order derivatives. In this Thesis we present Adams-type inequalities for unbounded domains in Rn and some applications to existence and multiplicity results for elliptic and biharmonic problems involving nonlinearities with exponential growth